2013
DOI: 10.1186/1475-2891-12-84
|View full text |Cite
|
Sign up to set email alerts
|

Effect of green tea on reward learning in healthy individuals: a randomized, double-blind, placebo-controlled pilot study

Abstract: BackgroundBoth clinical and preclinical studies revealed that regular intake of green tea reduced the prevalence of depressive symptoms, as well as produced antidepressant-like effects in rodents. Evidence proposed that disturbed reward learning has been associated with the development of anhedonia, a core symptom of depression. However, the relationship between green tea and reward learning is poorly investigated. Our goal was to test whether chronic treatment with green tea in healthy subjects affects the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Extracts from gotu kola ( Centella asiatica ; Bradwejn, Zhou, Koszycki, & Shlik, ), green tea ( Camelia sinensis ; Zhang et al, ), holy basil ( Ocimum sanctum ; Sampath, Mahapatra, Padhi, Sharma, & Talwar, ), and Sceletium tortuosum (Terburg et al, ) when administered to healthy adults were more effective than placebo in reducing anxiety and/or depression scores.…”
Section: Resultsmentioning
confidence: 99%
“…Extracts from gotu kola ( Centella asiatica ; Bradwejn, Zhou, Koszycki, & Shlik, ), green tea ( Camelia sinensis ; Zhang et al, ), holy basil ( Ocimum sanctum ; Sampath, Mahapatra, Padhi, Sharma, & Talwar, ), and Sceletium tortuosum (Terburg et al, ) when administered to healthy adults were more effective than placebo in reducing anxiety and/or depression scores.…”
Section: Resultsmentioning
confidence: 99%
“…The results show chronic treatment of green tea increased reward learning compared with placebo by decreasing the reaction time in monetary incentive delay task. Moreover, participants treated with green tea showed reduced scores measured in MADRS and HRSD-17 compared with participants treated with placebo [27].…”
Section: Antidepressant Effects Of Tea Consumption In the Literaturementioning
confidence: 99%
“…Interestingly, a large longitudinal study showed that caffeinated coffee consumption is associated with a reduced risk of depression (Lucas et al, 2011). It was also reported that ingestion of green tea has a preventative effect on the development of depression in mice and humans Zhang et al, 2013). Therefore, there is considerable evidence that some dietary phytochemicals protect the brain against stress.…”
Section: Psychologic Stressmentioning
confidence: 99%